P-414 Ultrastructural and functional defects in cilia of endometrial glands from women with reproductive failure. (30th June 2022) - Pearson-Farr, J; Doherty, R; Chatelet, D; Goggin, P; Ng, B; Lucas, J; Cleal, J; Lewis, R; Cheong, Y
Abstract: Study question: Do endometrial gland factors influence pregnancy success? Summary answer: Increased proportion of cilia defects during the window of implantation in endometrial glands from women with reproductive failure compared to controls What is known already: Endometrial glands are important for embryo implantation and successful pregnancy. There is an unmet clinical need to relate endometrial gland structure to function, identify markers for reproductive failure and targets for therapeutic interventions. Ciliated epithelial cells in the endometrium are a distinct cell type with a particular cell transcriptomic signature. Cilia defects have been reported in endometrial glands from women with reproductive failure however, a quantitative study of cilia defects in endometrial glands is yet to be established. Study design, size, duration: An observational study comparing women with subfertility, recurrent pregnancy loss and controls Participants/materials, setting, methods: Endometrial samples were collected during the implantation period from fertile controls (n = 10), women with subfertility (n = 11) and women with recurrent pregnancy loss (n = 15). Ciliated cells in endometrial glands were imaged by transmission electron microscopy and the proportion of cilia defects were quantified and compared between study groups. Endometrial glands were isolated from endometrial biopsies and the cilia beat frequency of ciliated cells was quantified by high-speed video analysis. Main results and the role of chance: Our study reports a significant increase in the proportion of cilia ultrastructural defects in endometrial glands from women with subfertility versus fertile controls (P < 0.05). Cilia defects included microtubule disarrangement, transposition and loss of cilia inner dynein arm motor proteins. Ciliated cells in endometrial glands from women with recurrent pregnancy loss demonstrated a higher proportion of defects compared to fertile controls but this did not reach statistical significance (P = 0.07). A significant decrease in cilia beat frequency was reported in ciliated cells of endometrial glands from women with subfertility compared to fertile controls (P < 0.05). Limitations, reasons for caution: This is an observational study with a relatively small sample size however, the participants in the study and control groups were matched for age, BMI and menstrual cycle characteristics. Wider implications of the findings: This study quantified ultrastructural and functional differences of ciliated cells in endometrial glands from women with reproductive failure. Endometrial glands with perturbed cilia structure and function may be non-conductive to successful pregnancy. Differences in endometrial gland cilia could be used to identify a perturbed endometrium and develop targeted therapies. Trial registration number: not applicable